2012
DOI: 10.1063/1.3692292
|View full text |Cite
|
Sign up to set email alerts
|

A DFT+U study of acetylene selective hydrogenation on oxygen defective anatase (101) and rutile (110) TiO2 supported Pd4 cluster

Abstract: The reaction mechanisms for selective acetylene hydrogenation on three different supports, Pd(4) cluster, oxygen defective anatase (101), and rutile (110) titania supported Pd(4), cluster are studied using the density functional theory calculations with a Hubbard U correction (DFT+U). The present calculations show that the defect anatase support binds Pd(4) cluster more strongly than that of rutile titania due to the existence of Ti(3+) in anatase titania. Consequently, the binding energies of adsorbed species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 54 publications
1
34
0
Order By: Relevance
“…Aside from the numerous studies that have been done onethylene adsorption on metal andtransition metal surfaces [6,[12][13][14][15][16][17][18], ethylene adsorption on metal oxide surface is a topic that also received quite significant amount of attention [9,[19][20][21][22]. In particular for ethylene interaction with TiO 2 , several studies -in which most of them are experimental works -have been carried out [7,9,19,20,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the numerous studies that have been done onethylene adsorption on metal andtransition metal surfaces [6,[12][13][14][15][16][17][18], ethylene adsorption on metal oxide surface is a topic that also received quite significant amount of attention [9,[19][20][21][22]. In particular for ethylene interaction with TiO 2 , several studies -in which most of them are experimental works -have been carried out [7,9,19,20,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Models that gradually start to integrate support effects rely typically either on fully periodic film formulations, in which several layers of the active phase are deposited on a periodically modeled support, 24 or on approaches in which finite clusters are deposited on a periodically modeled support. [25][26][27][28][29] The first approach is most interesting from a computational point of view, as it only requires relatively small unit cells. On the other hand, results obtained in this way may be severely affected by the (spurious) strain that is imposed by the lattice mismatch between the active phase and the support, or by a falsified charge transfer due to electrostatic effects between the periodic image cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Wang et al [67] systematically studied the crystal plane effect on the stability of NPs using anatase (101) and rutile (110) TiO 2 by density functional theory (DFT) calculation. They found that the absorption energies of the Pd 4 cluster on defective anatase (101) and rutile (110) TiO 2 showed an obvious difference (-4.53 and -3.19 eV, respectively), which indicates a stronger interaction between Pd 4 cluster and anatase (101) TiO 2 compared to that of the rutile (110) TiO 2 .…”
Section: Anchoring Nanoparticles At Special Sites or On Crystal Planesmentioning
confidence: 99%